Tradition and transformation : a critique of English setwork selection (2009-2011). - Silverthorne, Rosemary Ann (My University, 2010)
This Research Report critiques the English Home Language Literature setwork selection for the period 2009-2011 in terms of the National Curriculum Statement for English Home Language for Grades 10- 12 to establish whether there is consonance between policy and practice in this section of the syllabus and to determine whether the new national syllabus offers a traditional or a transformational approach to the subject. In order to do this, the National Curriculum Statement is analysed in terms of the principles and outcomes which it intends to be actualised in the study of English and selects those that seem applicable to literature studies. Questions are formulated encapsulating these principles and used as the tools to critique the new national literature syllabus both as regards its individual constituent parts and as regards the syllabus as a whole. A brief comparison between the current prescribed literature selection and setworks set from 1942 to the present day establishes whether the new syllabus has departed from old syllabus designs, whether it acknowledges the new target group of pupils in multiracial English Home Language classrooms by offering a revised, wider and more inclusive selection of novels, dramas, poems and other genres such as short stories, or whether it remains traditionally Anglocentric in conception. The conclusions reached are that although the setworks conform to the letter of the requirements set down in the NCS, the underlying spirit of transformation is not realised. The inclusion of some poets from Africa and South Africa is merely content addition to a Eurocentric core curriculum, a form of tokenism which does not reorientate the syllabus significantly or move it away from its traditional trajectory. The report suggests that literature of merit from both Africa and South Africa be included in every part of the syllabus so that it reflects in some degree the contributions that the continent makes to English literature, in this way including in its scope the interests and identities of the wide range of learners studying English Home Language in the South African context.
Keywords: Curriculum; Syllabus; Setwork; National Curriculum Statement; Learning Programme Guidelines; Home language; Tranformation; Tradition